2021
DOI: 10.1002/app.51171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crosslinked polycarboxylate superplasticizers with crosslinking agent containing ester and amide groups on the properties of cementitious systems

Abstract: Herein, crosslinked polycarboxylate superplasticizers were synthesized using acrylic acid, sodium methylallyl sulfonate and methyl polyethylene glycol acrylate as monomers, and monomers that contain either ester or amide groups as crosslinking agents. The superplasticizers that were synthesized from the ester-and amide-based crosslinking agents were respectively denoted as SP-E and SP-N. In addition, a series of performance characterizations were carried out to explore the influence of different functional gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A considerable amount of research has been conducted to develop highperformance PCEs with different backbones, different side chain lengths, and different functional groups in order to improve the fluidity and high strength of concrete at low water to cement ratios during its application process [6][7][8][9][10][11][12][13]. The ester functional group in PCEs has been reported to have various functions when they are applied in concrete, such as slump retention, retardation, and viscosity reduction [14][15][16][17]. For example, the slump-protecting PCE was synthesized via the copolymerization reaction of poly(ethylene glycol) methyl ether methacrylate, acrylic acid (AA), and ester or amide groups by Lin's group, which not only improves the dispersion performance but also has an excellent slump-protecting effect [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable amount of research has been conducted to develop highperformance PCEs with different backbones, different side chain lengths, and different functional groups in order to improve the fluidity and high strength of concrete at low water to cement ratios during its application process [6][7][8][9][10][11][12][13]. The ester functional group in PCEs has been reported to have various functions when they are applied in concrete, such as slump retention, retardation, and viscosity reduction [14][15][16][17]. For example, the slump-protecting PCE was synthesized via the copolymerization reaction of poly(ethylene glycol) methyl ether methacrylate, acrylic acid (AA), and ester or amide groups by Lin's group, which not only improves the dispersion performance but also has an excellent slump-protecting effect [6].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that PCEs prepared using esters have better performance than those synthesized using amides. Therefore, they also used trimethylolpropane triacrylate and trimethylolpropane ethoxylate triacrylate to prepare four PCEs containing ester groups [15]. They concluded that PCEs with higher ethoxy group contents exhibited better workability.…”
Section: Introductionmentioning
confidence: 99%
“…PCE superplasticizers were used to modify the surface of the sand in the preparation of the cement mortar and increased its compressive strength at 7 and 28 days of age (Noaman et al, 2020). Cement pastes treated with polycarboxylate synthesized with ester-based had better behaviour of dispersibility, fluidity retention and viscosity than those treated with polycarboxylate with amide-based (Lin et al, 2021). PCE copolymers based on isoprenyl ether, vinyl, allyl, and methacrylate macromonomers were synthesized and it was found that those with higher hydrophilic-lipophilic balance (HLB) values significantly reduced the plastic viscosity of mortars and concretes and low water-to-cement ratios.…”
Section: Introductionmentioning
confidence: 99%